Feministische Interpretationen des zweiten Schöpfungsberichts im Lichte der allgemeinen Feminismuskritik Judith Butlers (lectio difficilior, 2007)
Genesis 2-3 has always been a text to which feminism and especially feminist theology has paid special attention because it is one of the main passages of the canon that deal directly with the relationship between the sexes. One of the main goals of feminist exegesis has been to overcome the predominance of the traditional, patriarchal interpretations of the text by developing alternative, feminist readings, and it is (or should be) widely acknowledged that they have successfully done so. But what I want to show is that if one steps back from the theological perspective for a moment and examines the common feminist interpretations from a philosophical point of view, more precisely in the light of the general critique of traditional feminism brought forward by the philosopher Judith Butler in her well-known book “Gender Trouble”, one might nevertheless be worried if feminist critique has gotten far enough in their re-interpretation of Genesis 2-3.